Pengenalan Digital Marketing Bagi Pelaku Usaha UMKM Di Wilayah Desa Jembrak Kecamatan Pabelan Kabupaten Semarang - Mukhamad Kholil A; Bima Prahar Adilase; Ganda Subrata (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2022)
Digital marketing promotion media is expected to be an effective choice for UMKM in developing its business and reaching national and international markets. Conventional promotional media costs a lot and is far away more complicated by itself and is no longer a major concern for UMKM players because of digital marketing. The purpose of this activity is to help UMKM business actors use social media as a means for them to carry out promotions and so on. Provide an understanding of the importance of digital marketing in the introduction of their products widely. Can be used as a motivation for them to introduce their products widely. In general, the implementation of this community service activity has gone well. I would like to thanks to the cooperation between the committee and the support of various parties. However, there were a number of things to note after the activity took place, namely, the training participants needed continuous assistance after this activity, because there were still many training participants who were unable to design persuasive messages and utilize digital marketing and other media.